PERUBAHAN KADAR HEMOGLOBIN PADA IBU KALA I FASE AKTIF KE 6 JAM POST PARTUM DI WILAYAH KERJA PUSKESMAS ARJASA TAHUN 2019 - Septi Permatasari; Jamhariyah Jamhariyah; Lulut Sasmito (Jurnal Bakti untuk Negeri, 2022)
In 2017 post partum bleeding in Indonesia reached 26,28% or as many as 139 people . This study aims to determine the change in hemoglobin levels in the mother during the first active phase to 6 hours post partum. This type of research is a comparative study with the one group pre test and post test methods. The inpartu mother population of 39 respondents, based on sampel criteria obtained by 35 respondents with incidental sampling techniques. The research instrument uses an observation sheet with an Hb Digital Quick-Check. To measure hemoglobin levels ibu inpartu during first active phase and 6 hours post partum. Data analysis using test T sample pairs, with the help of the SPSS program. The results showed the average value of maternal hemoglobin levels during the active phase 12,29 gr/dL. While the average hemoglobin level in mothers 6 hours post partum obtained an average value of 11.94%. Based on the results of the statistic test, the p value = 0.013< 0.05, then H0 was rejected and Ha was accepted, which means that there is a change in hemoglobin levels in the mother during the active phase to 6 hours post partum in the Arjasa Health Center Work Area in 2019. Changes in hemoglobin levels in the 6 hours post partum experienced by most post partum mothers due to the opening of blood vessels former placenta implantation and the process of diuresis.